Radiology and endoscopy in acute upper gastrointestinal bleeding. - Fraser, G M (1976)
Of 112 patients admitted with acute upper gastrointestinal bleeding, the presumed bleeding site was detected in 61-5% of cases by radiology and in 57% of cases on endoscopy. Thirty-one patients who had barium-meal examination were operated on and the surgical and radiological findings agreed in 26 (84%). Twenty-three patients who had endoscopy were operated on and the surgical and endoscopic findings agreed in 15 (65%). In 10 cases radiology detected a lesion not identified on endoscopy and in nine endoscopy detected a lesion not seen at radiology. We suggest that when there are two potential sources of bleeding radiology as well as endoscopy can detect the actively bleeding lesion. The supplementary nature of radiology and endoscopy is emphasised and we conclude that both methods should be used if there is any doubt at the initial radiological or endoscopic examination about the source of the bleeding.